Mutations in SLC25A22: hyperprolinaemia, vacuolated fibroblasts and presentation with developmental delay. Issue 3 (2nd March 2017) - Reid, Emma S.; Williams, Hywel; Anderson, Glenn; Benatti, Malika; Chong, Kling; James, Chela; Ocaka, Louise; ,; Hemingway, Cheryl; Little, Daniel; Brown, Richard; Parker, Alasdair; et al.
Abstract: Mutations in SLC25A22 are known to cause neonatal epileptic encephalopathy and migrating partial seizures in infancy. Using whole exome sequencing we identified four novel SLC25A22 mutations in six children from three families. Five patients presented clinical features similar to those in the literature including hypotonia, refractory neonatal‐onset seizures and developmental delay. However, the sixth patients presented atypically with isolated developmental delay, developing late‐onset (absence) seizures only at 7 years of age. Abnormal metabolite levels have not been documented in the nine patients described previously. One patient in our series was referred to the metabolic clinic because of persistent hyperprolinaemia and another three had raised plasma proline when tested. Analysis of the post‐prandial plasma amino acid response in one patient showed abnormally high concentrations of several amino acids. This suggested that, in the fed state, when amino acids are the preferred fuel for the liver, trans‐deamination of amino acids requires transportation of glutamate into liver mitochondria by SLC25A22 for deamination by glutamate dehydrogenase; SLC25A22 is an important mitochondrial glutamate transporter in liver as well as in brain. Electron microscopy of patient fibroblasts demonstrated widespread vacuolation containing neutral and phospho‐lipids as demonstrated by Oil Red O and Sudan Black tinctorial staining; this might be explained by impaired activity of the proline/pyrroline‐5‐carboxylate (P5C) shuttle if SLC25A22 transports pyrroline‐5‐carboxylate/glutamate‐γ‐semialdehyde as well as glutamate.